Diffuse Supravalvular Aortic Stenosis: Surgical Repair in Adulthood - Giovanni Ferlan; Claudio De Pasquale; Concetta Losito; Annalisa Fiorella; Nicola Marraudino; Francesco Tunzi (Cardiology Research and Practice)
We present the case of a 54-year-old woman in which a diffuse congenital supravalvular aortic stenosis (SVAS) was associated with a severe aortic valve incompetence and heavy calcification of the aortic annulus. Repair consisted in resection of the ascending aorta, patch augmentation of the hypoplastic aortic root and annulus, placement of a 20 mm Dacron tubular graft (Vascutek, Renfrewshire, UK) and aortic valve replacement with a mechanical prosthesis (Sorin, Turin, Italy). Follow-up echocardiography demonstrated normal prosthetic valve function and a postoperative three-dimensional computed tomographic scan showed a normal shape of the reconstructed ascending aorta.